2021
DOI: 10.1128/msystems.01192-20
|View full text |Cite
|
Sign up to set email alerts
|

Heritable Gut Microbiome Associated with Salmonella enterica Serovar Pullorum Infection in Chickens

Abstract: Pullorum disease is one of the most common diarrhea-related diseases caused by Salmonella enterica subspecies enterica serovar Gallinarum biovar Pullorum (S. Pullorum); it negatively affects the poultry industry. However, limited studies have explored the association between the gut microbiota and S. Pullorum infection in chickens. In the present study, we performed a microbiome comparison and a microbiome genome-wide association study (mGWAS) to investigate the association among the host genetics, the gut mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 56 publications
1
18
0
Order By: Relevance
“…After invading the digestive tract of chicks, S. pullorum preferentially targets the cloacal bursa and spleen prior to eliciting inflammation in the intestine and causing systemic infection ( Shivaprasad and Barrow, 2007 ; Ding et al., 2021 ). The immunity of young chicks is extremely immature and, therefore, not able to trigger a cellular immune response robust enough to avoid systemic infection.…”
Section: Discussionmentioning
confidence: 99%
“…After invading the digestive tract of chicks, S. pullorum preferentially targets the cloacal bursa and spleen prior to eliciting inflammation in the intestine and causing systemic infection ( Shivaprasad and Barrow, 2007 ; Ding et al., 2021 ). The immunity of young chicks is extremely immature and, therefore, not able to trigger a cellular immune response robust enough to avoid systemic infection.…”
Section: Discussionmentioning
confidence: 99%
“…While other studies have reported negative or positive correlations between intestinal community composition, abundance of specific genera/species and Salmonella abundance or prevalence ( Videnska et al, 2013 ; Azcarate-Peril et al, 2018 ), this has been a tenuous association as reflected in comparisons among studies ( Azcarate-Peril et al, 2018 ; Ma et al, 2020 ; Mon et al, 2020 ) and trials ( Videnska et al, 2013 ). The exclusive genera/species, identified in this study, have been associated with Salmonella exclusion in some studies ( Pourabedin et al, 2017 ; Liu et al, 2018 ; Khan and Chousalkar, 2020 ; Ding et al, 2021 ), but absent in others ( Videnska et al, 2013 ; Azcarate-Peril et al, 2018 ; Ma et al, 2020 ; Mon et al, 2020 ). The genera/species, identified in this study, that negatively correlate with Salmonella are also absent in a competitive exclusion product known to effectively reduce Salmonella colonization in poultry ( Pedroso et al, 2016 ).…”
Section: Discussionmentioning
confidence: 53%
“…These genera or species have also been associated with enteropathogen colonization or intestinal health in other studies ( Antharam et al, 2013 ; Miquel et al, 2013 ; Rossi et al, 2014 ; Stanley et al, 2014 ; Xu et al, 2014 ; Thibodeau et al, 2015 ; Knoll et al, 2016 ). Others have also noted absence or reduced abundance of F. prausnitzii and member species of the clostridial families ( Collins et al, 1994 ) Lachnospiraceae (XIV) and Ruminococcaceae (III/IV) in birds colonized with Salmonella ( Pourabedin et al, 2017 ; Liu et al, 2018 ; Khan and Chousalkar, 2020 ; Ding et al, 2021 ). Several of these species, associated with exclusive communities but absent from the Salmonella permissive community, may play an anti-inflammatory role in maintaining intestinal homeostasis and health ( Wu and Wu, 2012 ; Miquel et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…The sequencing and barcode primers were removed from the reads for the identification of the V4 sequence. The sequence reads were filtered by related settings, as in our previous study [22]. Briefly, the pair‐end sequence reads passed our quality control standards (average mass >30, sequence length >50) and was assembled according to their overlapping sequences.…”
Section: Methodsmentioning
confidence: 99%